Development of Creative Industries as A Multiplier Effect of Shadow Puppet Performances Resists the Plague in Pandanan Village, Soropaten, Klaten District - Murdowo, Drajat Agus; Satiyoko, Yohanes Adhi; Sumiyardana, Kustri; Basori, Basori; Wewengkang, Nontje Deisye; Yono, Sri (ETNOSIA : Jurnal Etnografi Indonesia, 2024)
Leather puppets performances have been carried out for generations in Pandanan Village, Klaten Regency as a ritual to repel disease outbreaks. Regular performances are held every month of Sura, but leather puppet performance ia also held every Friday Pon night. Local people are involved as ritual performers, spectators, and traders in the leather puppet performance. Along with suggestion of UNESCO to develop economy based on local culture, the leather puppets performance is developed in any creative industries. This study aims to explore leather puppet performance and the strategies for vitalizing the potential of leather puppets into the creative industry. Using qualitative approach, this study was conducted in Padanan village, Kabupaten Klaten, Central Java, Indonesia. Data collection methods include observation and interview. Those who participated in this study consists of village head, local figures, dalang (puppeter), pengrawit (gamelan players), souvenir sellers, and spectators. The result shows that leather puppets performance that has changed their function from ritual tradition to repel disease outbreaks into tradition to “asking blessed” by the puppeters (dalang), and finally it turns to traditional performance that brings not only culture entertainment but also creating market economy. This situation is potential to develop creative economy based on local culture by developing creative industries as stated by UNESCO in order to enhance local economy.